IAPP blocks anti-breast cancer function of CD8+T cells via targeting cuproptosis - Guo, Dandan; Huang, Zhijian; Wang, Qianqian; Chen, Wei; Huang, Yu; Sun, Xinhao; Chen, Jian; Feng, Shuying (Frontiers in Immunology, 2024)
BackgroundBreast cancer (BRCA) is the most prevalent type of cancer worldwide. As a highly heterogeneous cancer, it has a high recurrence rate. Since its biological behavior can be regulated by immunity and cuprotosis, so exploring potential therapeutic target to mediate immunity and cuprotosis is of great significance for BRCA therapy.MethodsThe immune-related genes and immune-cuprotosis-related deferentially expressed genes (ICR-DEGs) were identified by mining the TCGA database. Prognostic analysis, differential expression analysis, univariate and lasso regression analyses were used to determine their independent prognostic values. To evaluate the relationship between ICR-DEGs and immune scores, we constructed a prognostic risk model to evaluate immune checkpoints, and then the role of tumor immune microenvironment in BRCA was explored. Furthermore, anti-BRCA function and mechanism of islet amyloid poly-peptide (IAPP) mediated CD8+T cells were verified by means of flow cytometry, ELISA, and subcutaneous transplantation tumor model.ResultsAll results suggested that immune-cuprotosis-related genes were a potential predictor of BRCA’s response to immune checkpoint inhibitors and immunotherapy biomarkers. Thereby downregulation of IAPP reduced cuprotosis of CD8+T or Her2-CAR-T cells to promote the anti-BRCA function both in vitro and in vivo.ConclusionOur research had clarified the function and mechanism of IAPP in CD8+T cells, providing new ideas for improving the diagnosis and treatment of BRCA.